Dynamic Analysis Of Exports, Imports, And Gross Regional Domestic Product (Grdp) In Maluku Province: A Vector Error Correction Model (Vecm) Approach - Christianto Leasiwal, Teddy; Assel, M.Ridhwan; Christianty, Restia (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the impact of exports and imports on the Gross Regional Domestic Product (GRDP) of Maluku Province using the Vector Error Correction Model (VECM) approach. Time series data were tested for stationarity using the Augmented Dickey-Fuller (ADF) test, which showed that GRDP, exports, and imports are stationary at the first difference. The Johansen cointegration test confirmed a long-run equilibrium relationship among the three variables, while the optimal lag length was determined to be four periods. Granger causality tests indicated a one-way causality from GRDP to exports and from imports to GRDP. The VECM estimation revealed that, in the long term, exports have a positive and significant effect on GRDP, with a 1% increase in exports leading to a 0.062362% rise in GRDP. In contrast, imports have a negative but statistically insignificant effect, where a 1% increase in imports corresponds to a 0.075382% decrease in GRDP. These findings highlight the importance of strengthening the export sector to drive economic growth in Maluku Province, while the impact of imports should be managed to prevent adverse effects on sustainable GRDP growth.